BS 5911-1:2021. Concrete pipes and ancillary concrete. Part 1: Specification for unreinforced and reinforced concrete pipes (including jacking pipes) and fittings with flexible joints (complementary to BS EN 1916:2002) (1st March 2021) - British Standards Institution,
No abstract available